Does attachment to God matter? Role of spiritual attachment in mental health through self-forgiveness: lessons from Turkish college sample - Aydın, Fatih (Frontiers in Psychology, 2025)
BackgroundThe present study examines the role of spiritual attachment and self-forgiveness in flourishing among college students. A mediation model was tested in which flourishing served as the outcome variable, spiritual attachment as the independent variable, and self-forgiveness as the mediator.MethodsThe sample consists of 311 (72.3%) females and 119 (27.7%) males, totaling 430 volunteered college students from 58 colleges and 18 faculties in Türkiye. The average age was 21.52 (3.49) for the total sample. Demographic Information Form, the Flourishing Scale, the Muslim Spiritual Attachment Scale, and the Self-Forgiveness Dual-Process Scale were utilized for data collection. A mediation model was tested based on the distinct subscales of self-forgiveness: value reorientation and esteem restoration.ResultsThe findings demonstrated that spiritual attachment significantly predicts flourishing among college students. Furthermore, both value reorientation and esteem restoration significantly predicted flourishing and played a mediator role in the relationship between spiritual attachment and flourishing.ConclusionTogether, it can be concluded that greater spiritual attachment may directly and indirectly (via self-forgiveness) contribute to better mental functioning in life. The present study promises some valuable information for practitioners in the field on the role of spiritual attachment and self-forgiveness in the mental health of emerging adults.